2017
DOI: 10.1039/c6sc04966d
|View full text |Cite|
|
Sign up to set email alerts
|

Electrochemical promotion of catalysis over Pd nanoparticles for CO2 reduction

Abstract: Electrochemical promotion of catalysis was observed over Pd nanoparticles with a significant rate enhancement ratio (ρ) for catalyzing CO2 reduction to produce formate in 1 M KHCO3 solution at ambient temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 46 publications
4
66
0
Order By: Relevance
“…Selective CO 2 reduction to formic acid has also been studied on other metal clusters,, metal complexes, ionic liquids, transition metal surfaces,, metal‐hydride, and surfaces of In 2 O 3 , CeO 2 , ZnO etc ,. On the Cu‐hydride nanocluster, CO 2 reduction follows a different mechanism where CO 2 is activated in the influence of lattice hydride and forms a formate intermediate at an overpotential of 0.32 eV .…”
Section: Introductionmentioning
confidence: 99%
“…Selective CO 2 reduction to formic acid has also been studied on other metal clusters,, metal complexes, ionic liquids, transition metal surfaces,, metal‐hydride, and surfaces of In 2 O 3 , CeO 2 , ZnO etc ,. On the Cu‐hydride nanocluster, CO 2 reduction follows a different mechanism where CO 2 is activated in the influence of lattice hydride and forms a formate intermediate at an overpotential of 0.32 eV .…”
Section: Introductionmentioning
confidence: 99%
“…22 They also proved that the Pd-Pt bimetal could signicantly reduce the production of H 2 and enhance CO 2 reduction. 23 The 49 nm Au@Pd@Pt NRs exhibited maximum catalytic activity when q Pt was 0.5; this implied that the ratio of their Pt-cluster to Pd shell was optimal for the electroreduction of CO 2 . This core-shell-cluster nanostructure is completely different from other bimetallic and trimetallic alloy/composite nanostructures because the proportions of the core, shell and cluster can be subtly tuned independently to utilize the synergistic effect for maximum enhancement.…”
Section: Resultsmentioning
confidence: 97%
“…At the beginning of the electrolysis, the highest current density was observed with the monometallic Pd catalyst; however, it gradually decreased during the electrolysis for 5 h. According to the literature, this deactivation is considered to be due to poisoning of the catalyst by CO which generates as an intermediate species of CO 2 reduction. 9,[12][13][14] Since the adsorption strength of CO to Pd is too strong, CO once formed occupies the active sites and prevents the accomplishment of the catalytic cycle. In contrast, the Cucontaining catalyst did not show the deactivation over the electrolysis.…”
Section: Product Analysismentioning
confidence: 99%
“…Therefore, considerable efforts have been made to develop a variety of electrocatalyst that can be operated at small overpotential. [4][5][6][7][8] Recently, it has been reported that Pd nanoparticles show remarkable activity toward reduction of CO 2 to formate, [9][10][11][12][13][14][15] which can be used as a hydrogen carrier, a fuel in direct formic acid fuel cells and a chemical feedstock for the synthesis of fine chemicals. [16][17][18][19][20][21] Formate production by Pd nanoparticles can proceed close to the thermodynamic potential, and their selectivity for the reduction of CO 2 to formate is quite high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation